Identification of candidate single nucleotide polymorphic markers in brown-marbled grouper Epinephelus fuscoguttatus (Forsskal, 1775) - Mohamad Tahir, Nur Diyana (2021)
Brown -marbled grouper Epinephelus fuscoguttatus is a premium marine food fish with high demand in Asia. However, its aquaculture development is limited by broodstock availability with heavy reliance on wildstocks. The growth and stress polymorphic markers were explored using high-throughput sequencing and the genetic diversity of E. fuscoguttatus for potential use in selective breeding to facilitate the development of aquaculture. Thus, the first objective of this study was to investigate the salinity tolerance of E. fuscoguttatus and its effects on the serum cortisol levels, survival and growth in an aquaria setting. This was a preliminary study towards the identification of SNP markers later on. In this study, grouper juveniles (92.43 ± SEM 0.51 mm) were maintained in 31 ppt seawater for one-week acclimatization and transferred into five tanks with different seawater dilutions (5, 10, 15, 20, 25 ppt). The results revealed that serum cortisol of fish in high change of salinity (from 31 ppt to 15, 10 and 5 ppt) was significantly higher than the control group immediately after exposure. In the higher salinity change (from 31 to 5 ppt), the survival percentage was 50%, while no mortality observed in the lower change of salinity. Whereas after 2 weeks, a significant difference in the decrease of mean weight of fish in the higher change of salinities (from 31 to 15 ppt, 10 ppt, and 5 ppt) was observed compared to the control group indicating the effects of chronic stress on the growth performance of fish. In the aquaria experiment, some fish were more stress-tolerant than others could be used as potential as candidate for selective breeding. The second objective of this study was to measure the growth performance of E. fuscoguttatus in sea cage culture to detect the slow and fast growers for DNA sequencing. The fish were grown for 10 months in a floating cage where the morphometrics of 100 fish (215.10 ± SEM 21.64 mm) were measured and 20 fish were intramuscularly microchipped. At the end of 10 months, 10 fish recovered with microchip were categorized based on their size as fast- and slow-growers and processed for DNA extraction. The next objective was to assess the potential of a novel high-throughput sequencing method on the muscle DNA samples. Highthroughput sequencing using the double digestion restriction associated DNA sequencing (ddRADSeq) was done utilising two restrictive enzymes: PstI and MspI. The results showed 146,244 sequences and with 16172 SNP of 25 or less per sequence. Out of the 16172 SNP, 64% were identified with one SNP, while 5776 (35%) were identified with more than two SNPs. An overall FST for the two populations of fast- and slow-growers was extremely low (0.0705) with 21.2% - 26.1% polymorphic loci and high observed homozygosity as calculated by STACKS indicating inbreeding. The last objective of this study was to analyse the genetic diversity of E. fuscoguttatus and isolate and identify SNP markers using bioinformatic tools as candidate markers. Analysis of the 382 filtered SNP sequences using BLAST, GO and UniProt databases revealed 36 sequences which matched the Epinephelus spp. and 18 GO biological processes of 57 genes in the fast-and slowgrowers related to growth and stress. Sequencing using the novel ddRAD Seq revealed four genes: acss2, abhd15, lrp2 and pdp1 as potential candidate markers that could assist in the selection of broodstock fish with superior traits. This is the first ddRADSeq performed in this species. The outcome of this study can contribute to understanding suitable bioinformatics pipelines, further adding to the limited genetic information available for establishing and identifying suitable markers for the future of assisted selective breeding of this species.